2023
DOI: 10.3389/fnut.2023.1183973
|View full text |Cite
|
Sign up to set email alerts
|

The association of handgrip strength with all-cause and cardiovascular mortality: results from the National Health and Nutrition Examination Survey database prospective cohort study with propensity score matching

Lijiao Xiong,
Zhaohao Zeng,
Shuojia Wang
et al.

Abstract: ObjectiveTo investigate the association between handgrip strength (HGS) with all-cause and cardiovascular disease (CVD) mortality in US adults.MethodWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) prospective cohort study (2011–2014) with 10,470 participants. The cox regression analysis, Kaplan–Meier survival curves, fitted curves, ROC curves, and propensity score-matched analysis (PSM) with inverse probability of treatment weighting (IPTW), SMRW (PSM with repeated weights),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Handgrip strength (HGS) is widely recognized as an indicator of overall muscle strength and functional status, providing a valuable tool for assessing musculoskeletal health and predicting adverse health outcomes. Our previous research indicated a significant correlation between low HGS and an increased risk of all‐cause mortality and cardiovascular mortality in the American population 7 . Furthermore, we have identified a causal relationship between HGS and all‐cause mortality based on a Genome‐wide association study analysis of a population of 1.1 million Europeans 8 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Handgrip strength (HGS) is widely recognized as an indicator of overall muscle strength and functional status, providing a valuable tool for assessing musculoskeletal health and predicting adverse health outcomes. Our previous research indicated a significant correlation between low HGS and an increased risk of all‐cause mortality and cardiovascular mortality in the American population 7 . Furthermore, we have identified a causal relationship between HGS and all‐cause mortality based on a Genome‐wide association study analysis of a population of 1.1 million Europeans 8 .…”
Section: Introductionmentioning
confidence: 85%
“…Our previous research indicated a significant correlation between low HGS and an increased risk of all‐cause mortality and cardiovascular mortality in the American population. 7 Furthermore, we have identified a causal relationship between HGS and all‐cause mortality based on a Genome‐wide association study analysis of a population of 1.1 million Europeans. 8 Additionally, HGS serves as a predictor of hip fracture recovery and is associated with falls and fractures in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle plays a critical role in maintaining physical function and metabolic health (Wolfe, 2006). In this regard, a growing number of studies reveal that, in both middle-aged and older adults, strength and muscle mass are inversely associated with increased risk of chronic health problems such as diabetes (Moon, 2014;Kunutsor et al, 2021a;Boonpor et al, 2021), cardiovascular disease (Tyrovolas et al, 2020;Lopez-Jaramillo et al, 2022;Peralta et al, 2023), cognitive impairments (Filardi et al, 2022;Tessier et al, 2022;Prokopidis et al, 2023), falls (Landi et al, 2012;Reijnierse et al, 2019), bone fractures (Kunutsor et al, 2021b), disability (Abay et al, 2022), as well as all-cause and cause-specific mortality (López-Bueno et al, 2022;Landi et al, 2022;Xiong et al, 2023). In general, muscle strength is a better predictor of adverse health outcomes than muscle mass (Cruz-Jentoft et al, 2019).…”
Section: Introductionmentioning
confidence: 99%